2015
DOI: 10.3906/vet-1411-57
|View full text |Cite
|
Sign up to set email alerts
|

Influences of flunixin and tenoxicam on the pharmacokinetics of florfenicol in lipopolysaccharide-induced endotoxemia

Abstract: The purpose of this study was to investigate the influences of flunixin (FM) and tenoxicam (TN) on the pharmacokinetics of florfenicol (FF) after coadministration in lipopolysaccharide (LPS)-induced endotoxemic rabbits. Fifteen male rabbits were used in this study. FF (20 mg/kg), FM (2 mg/kg), and TN (1 mg/kg) were coadministered via intravenous injection to the animals. The concentrations of FF were determined by high-performance liquid chromatography with diode-array detection from 0.08 to 12 h in plasma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The distribution and elimination half‐lives, 0.132 ± 0.0289 hr and 2.78 ± 0.166 hr, were in agreement with results previously reported in pigs (Liu et al., ). Fast elimination was also observed in other species of animals, dog 3.09 ± 0.13 hr (Birdane & Birdane, ), chicken 0.73 ± 0.08 to 1.07 ± 0.07 hr (Poźniak et al., ), llamas 2.2 hr (Pentecost, Niehaus, Werle, & Lakritz, ), rabbit 2.69 ± 0.38 hr (Koç, Atila, Karakuş, & Üney, ), sheep 1.01 ± 0.09 hr (Lane et al., ), respectively.…”
Section: Discussionmentioning
confidence: 77%
“…The distribution and elimination half‐lives, 0.132 ± 0.0289 hr and 2.78 ± 0.166 hr, were in agreement with results previously reported in pigs (Liu et al., ). Fast elimination was also observed in other species of animals, dog 3.09 ± 0.13 hr (Birdane & Birdane, ), chicken 0.73 ± 0.08 to 1.07 ± 0.07 hr (Poźniak et al., ), llamas 2.2 hr (Pentecost, Niehaus, Werle, & Lakritz, ), rabbit 2.69 ± 0.38 hr (Koç, Atila, Karakuş, & Üney, ), sheep 1.01 ± 0.09 hr (Lane et al., ), respectively.…”
Section: Discussionmentioning
confidence: 77%
“…These changes may lead to the development of resistance to antibiotics, the emergence of undesirable effects, and a suboptimal level of drug exposure, leading to failure in the treatment of infection [28,29]. Although there are many studies investigating the effects of NSAIDs on the pharmacokinetics of antibiotics in healthy animals [30][31][32][33][34][35][36], studies conducted in the case of disease are limited [37][38][39]. We hypothesized that the effect of meloxicam on the pharmacokinetics of danofloxacin will change with the systemic inflammatory response caused by respiratory infection in lambs, and that the results obtained will contribute to the rational use of danofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a combined solution containing florfenicol 300 mg/mL and flunixin 16.5 mg/mL is commercially available for treating respiratory infections in cattle and pigs (Papich, 2018). Previous reports have shown that flunixin and tenoxicam modified the pharmacokinetics of florfenicol when these drugs were coadministered with this antimicrobial drug (Koc et al, 2015). Due to the inhibitory effects on renal prostaglandin synthesis, NSAIDs can decrease renal blood flow during infection and septic shock (Huh et al, 2013).…”
mentioning
confidence: 99%